Reference Values for Some Renal Function Parameters for Adult Population in North-Rift Valley, Kenya - Juma, Alice Atieno (Springer-Verlag, 2011)
A population based, cross-sectional study was carried out at Moi Teaching and Referral Hospital in collaboration with the Regional Blood Transfusion Center, North Rift. 367 participants (211 males and 156 females) were involved in the renal function reference range establishment. Reference ranges were constructed using non-parametric methods to estimate 2.5 and 97.5 percentiles of distribution as lower and upper reference limits, respectively. Results showed significant sex and age specific reference values in some of the established renal function parameters. North Rift Kenyan population clinical chemistry reference ranges differ from the American values commonly used in Kenyan Hospitals. The renal function reference values established in this study some of which are sex and age specific can be adopted for the North Rift Kenyan population.